Response to nitrogen fertilization of late-sown maize upon different winter previous crops - Salvagiotti, Fernando; Caviglia, Octavio; Bacigaluppo, Silvina; Barraco, Miriam Raquel; Boero, Leandro Ruben; Biassoni, María Micaela; Enrico, Juan Martin; Kehoe, Esteban; Eclesia, Roxana Paola; Madias, Andrés; Maltese, Nicolas; Melchiori, Ricardo Jose; et al. (Elsevier, 2025)
Agriculture is transitioning towards more sustainable ways of producing food, fiber, and biofuels, with practices aimed at conserving soil resources by prolonging soil occupation with cash or cover crops and balancing the proportion of cereals and winter legumes when increasing the number of crops in the rotation. Likewise, closing nutrient biogeochemical cycles is critical, particularly for N, which requires adjusting fertilizer rates to avoid surplus or soil mining. Winter crops for grain such as wheat (Triticum aestivum L.), pea (Pisum sativum L.), and for cover such as vetch (Vicia sativa L. or Vicia villosa L.) can differentially affect nitrogen (N) dynamics, yield response to N application, and associated efficiency metrics in succeeding late-sown maize (Zea mays L.). This study aimed to (i) quantify maize yield response to N fertilization by considering productivity, economic, and N efficiency metrics in late-sown maize following fallow or composing a double-crop after winter cash crops (wheat and field pea) or cover crop (vetch) and (ii) test whether vetch biomass can be used to predict the response to N fertilization. Forty on-farm trials were conducted under rainfed conditions in the Pampas region of Argentina during 13 seasons to test different N rates on late-sown maize yields growing after fallow, wheat, pea, or vetch. Maize grain yield was determined, and the agronomic and economic optimum N rates (AONR and EONR, kg fertilizer N ha−1), N use efficiency (NUE, kg of grain yield response per kg of N from fertilizer), and partial factor productivity (PFP, kg of grain produced per kg of N from fertilizer) were calculated. The results showed that (i) wheat caused a higher frequency (86 %) of yield response to N application in maize compared to other scenarios (average 60 %); (ii) no yield response to N was observed when soil N availability at sowing exceeded 175 kg N ha⁻¹ , regardless of the previous crop; (iii) maize following wheat showed the highest AONR and EONR, while maize following pea showed the lowest; (iv) there were no significant differences in NUE among winter crops, but the lowest PFP was observed after wheat; and (v) vetch biomass and N accumulation helped predict the yield response to N fertilization in the succeeding maize. We conclude that winter crops and their characteristics (e.g., wheat yield and vetch biomass) should be considered to fine-tune N fertilizer rates in late-sown maize, promoting the sustainability of the cropping system.